Anti-lawyers religion and the critics of law and state - Saunders, David, 1940- (London ; New York : Routledge, 1997)
Anti-Lawyers discusses how we should regard todays's critics of law and government in the light of the historical still unfinished struggle to separate the legal regulation of civil life from the Christian regulation of conscience.
Book Cover; Title; Contents; Foreword; Acknowledgements; RELIGION BY OTHER MEANS; INVISIBLE AND SPIRITUAL: VISIBLE AND EXTERNAL; CONSCIENCE AND LAW; THE COMMON LAWS CRITICS; THE COMMON LAWS DEFENDERS; RELIGION, LAW AND CIVIL MANNERS; SEPARATION OF POWERS; THE CONFESSIONAL STATE; CONFLICT OF CONFESSIONS; CONFLICT OF FACULTIES; SECTS, LAWS AND RIGHTS; THE LAW TRANSFORMED; THE LAWYER LOST; NOW THAT THE SAINTS ARE MARCHING IN; Notes; Bibliography; Index
Includes bibliographical references (p. 170-176) and index.
Description based on print version record.
Keywords: Church and state; Religion and law; Freedom of religion; LAW -- Discrimination; LAW -- Civil Rights; Electronic books